Clinical characterisation of human metapneumovirus infection in 525 patients with respiratory tract infections in Jilin province - Xiuhua Liu; Yang Liu; Jing Bian; Mengjuan Wang; Zhanxiu He; Huan Hu; Lei Zhang; Lei Zhang; Chaoying Liu (Frontiers in Cellular and Infection Microbiology)
BackgroundHuman metapneumovirus (HMPV) is a common cause of acute respiratory infections. The aim of this study was to analyze the demographic characteristics and treatment outcomes of HMPV virus infection in Jilin province.MethodsWe conducted a retrospective cohort analysis of patients with respiratory tract infections between September 2023 and February 2024 in the Lequn Campus of the First Hospital of Jilin University, using tNGS sequencing. This study focused on HMPV-infected patients and included infections with this virus alone as well as co-infections.ResultsIn the present study, 525 patients with respiratory diseases were analysed, 65 (12.57%) of whom were found to be infected with HMPV. The period of maximum human metapneumovirus infection was observed to be January, and of the 65 patients infected with this virus, 10 (15.2%) were infected with HMPV alone and 56 (84.8%) were co-infected with HMPV. The most prevalent co-infection was bacterial, with the most common identified pathogen being human herpesvirus, followed by Candida albicans and Streptococcus pneumoniae. The percentage of co-infections in patients not infected with HMPV was 78.87%. Patients infected with HMPV alone exhibited a lower proportion of males, elevated rates of fever and cough, and a higher prevalence of diabetes mellitus and CURB-65 score (P>0.05). The most prevalent initial diagnoses were pneumonia, with additional respiratory failure and hypoproteinaemia diagnoses. Furthermore, a higher proportion of patients infected with the HMPV virus were hospitalised for more than 10 days compared with those not infected with the virus.ConclusionHMPV is easily neglected in the current diagnosis and treatment process, but the risk it poses, such as long hospitalisation, should not be ignored. The tNGS showed excellent detection performance and great potential in this study, and it can be a good tool to help clinicians in diagnosis and treatment.